Report of the Working Group on Development of North Eastern Region During the Seventh Five Year Plan - Planning Commission (Planning Commission, 1985)
The Planning Commission constituted a Working Group on the Development of the North Eastern Region during the Seventh Five Year Plan,1985-90, with Shri P.H.Trivedi, Secretary, NEC as Chairman and Shri I.P.Gupta and after him Shri R.Vasudevan, Joint Secretary, Ministry of Home Affairs as member Secretary of it.
Planning Commission Government of India
Planning Commission Government of India